THE INTERFERENCE OF INDONESIAN GRAMMAR INTO THE ACQUISITION OF ENGLISH GRAMMAR (AN ANALYSIS OF THE 2ND SEMESTER STUDENTS’ WRITTEN TASK AT THE ENGLISH DEPARTMENT, UNIPDU JOMBANG) - Achmad Fanani (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2011)
Achmad Fanani University of Pesantren Tinggi Darul Ulum Jombang akufanani@gmail.com  Abstrak First Language (L1) has a significant effect on the second language (L2) acquisition. This kind of phenomenon in the study of second language acquisition is called the interference of first language into second language (negative Interlingua transfer). Such interference often leads to errors (Kreshen, Stephen, 1988). This study describes the interference of Indonesian language (L1) into the English language acquisition (L2) commonly made by the second – semester students of English Department, Faculty of Language and Letters, UNIPDU Jombang and the language – based factors that influence the occurrence of interference. key words: L1 interference, markedness, beginner– level students   Abstrak Bahasa pertama (L1) mempunyai dampak yang signifikan terhadap keberterimaan bahasa kedua (L2). Fenomena semacam ini dalam akuisisi bahasa kedua disebut dengan interferensi L1 kedalam L2 (Negative interlingual transfer). Interferensi tersebut seringkali mengakibatkan kesalahan (error) (Krasen, Stephen, 1988). Studi ini akan menggambarkan interferensi gramatika bahasa Indonesia ke dalam akuisi bahasa Inggris (L2) yang sering dilakukan oleh mahasiswa semester 2 Fakultas Bahasa dan Sastra UNIPDU Jombang serta faktor-faktor kebahasaan yang melandasi terjadinya hal tersebut. kata kunci: interferensi L1, penandaan, siswa pemula